A rare case of toxic epidermolysis necrolysis in early infancy: Successfully treated with intravenous immunoglobulin - Bharti Bhandari; Ragini Singh; Mritunjay Kumar; Aditya Saun (Wolters Kluwer Medknow Publications, 2019)
Toxic epidermal necrolysis (TEN) is a potentially life-threatening dermatological disorder characterized by widespread erythema, necrosis, and bullous detachment of the epidermis and mucous membranes, resulting in exfoliation and possible sepsis and/or death. TEN is a disease of both children and adults, but TEN in early infancy is a rare event; in literature, only few cases in infants aged <6 months have been reported so far. We reported a case of a 6-week-old infant who developed TEN after some local off-label medication for abdominal colic. After intravenous immunoglobulin treatment, the infant showed dramatic improvement without any complications.